EFISIENSI CABANG USAHATANI TALAS (COLOCASIA ESCULENTA(l)) DI KAMPUNG SAUF DISTRIK AYAMARU SELATAN KABUPATEN MAYBRAT - Evi Junike; Kunto Wibowo; Waromi, Josina (Sosio Agri Papua, 2023)
The taro farming branch activities carried out by the community in Sauf village, South Ayamaru District have been carried out for a long time and have been done regularly and passed down from generation to generation. This is because the role of taro is quite significant for farming families from an economic perspective and the food security of farming families. Thus, this research aims to determine the level of income and efficiency of the taro farming branch. The method used in this research is a descriptive method with a survey approach. The survey was conducted to determine the research location, namely Sauf Village, Ayamaru District and to determine the research subjects, namely taro farmers, who were taken using a simple random method. Primary data obtained through questionnaire-based interviews with 30 farmers was processed tabulatedly and analyzed using the B/C ratio. The research results show that the total income of taro farmers in one planting season is IDR 13,083,833 with an average per capita income of Rp. 436.128. To fullfill food needs, farming families use half of their production for family food. Furthermore, regarding the efficiency of the taro farming branch, the efficiency value of the taro farming branch is 3.10, which shows that the taro farming branch carried out by farmers in Sauf Village, South Ayamaru District is efficient. Efficiency occurs due to the use of relatively low variable costs, namely only transportation costs to the market, while the selection of seeds is taken from the plants before harvest, and there is no hired labor.